2020
DOI: 10.1152/ajprenal.00255.2020
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial transplantation by intra-arterial injection for acute kidney injury

Abstract: Acute kidney injury (AKI) is a common clinical disorder and one of the major causes of morbidity and mortality in the postoperative period. In this study, the safety and efficacy of autologous mitochondrial transplantation by intra-arterial injection for renal protection in a swine model of bilateral renal ischemia-reperfusion injury (IRI) was investigated. Female Yorkshire pigs underwent percutaneous bilateral temporary occlusion of the renal arteries with balloon-catheters. Following 60 minutes ischemia, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 47 publications
1
52
0
1
Order By: Relevance
“…There were two studies on experimental models of kidney focal ischemia in rats [ 43 ] and pigs [ 44 ], in which autologous mitochondria were injected intra-arterially.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were two studies on experimental models of kidney focal ischemia in rats [ 43 ] and pigs [ 44 ], in which autologous mitochondria were injected intra-arterially.…”
Section: Resultsmentioning
confidence: 99%
“…Jabbari et al [ 43 ] demonstrated that mitochondrial autografts from healthy muscle cells to injured kidney cells through injection into the renal artery prevented renal tubular cell death, restored renal function, ameliorated kidney damage, improved the regenerative potential of renal tubules, and decreased IRI-induced apoptosis [ 43 ]. Doulamis et al [ 44 ] investigated the safety and efficacy of autologous mitochondrial transplantation by intra-arterial injection for renal protection in a swine model of bilateral renal IRI. They found that the injected mitochondria were rapidly taken up by the kidneys.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to aging alterations the effect of diseases like diabetes on mitochondria is less clear [ 103 ]: Minet et al found in vitro impaired mitochondrial functions in type 2 diabetes-derived myotubes due to impaired ATP synthesis [ 104 ]. In diabetic rats, mitochondrial ATP content was lower compared to healthy individuals, whereas no obvious functional cardiac differences were seen [ 105 ]. In pathological diabetic conditions changes in morphology, superoxide production, cardiolipin content and dysfunctional mitochondrial protein import were seen in IMF of type 1 diabetic mice [ 106 , 107 , 108 ], whereas in type 2 diabetes the SSM seem to be more affected [ 109 ].…”
Section: Mitochondrial Agingmentioning
confidence: 99%
“…Mitochondrial transplantations have been so far successfully used in neurological fields [ 118 , 119 ], liver infarcts, kidney injuries [ 105 ], acute lung injury [ 120 ], acute limb injury [ 121 ] and in various cardiovascular settings. Especially in the field of cardiovascular research, interesting studies have been published during the course of the last years.…”
Section: Mitochondrial Transplantation For Heart Diseasesmentioning
confidence: 99%
See 1 more Smart Citation